INFLUENCE OF EXTERNAL FACTORS FOR MAKING DECISION IN PURCHASING NUVO SHOWER SOAP (A Case Study in District Consumer Mlati, Sleman regency, Yogyakarta) - Hastanto, Andri; Kahu Lantum, MS, Drs. Alex (Accounting, 2009)
Basically, the products offered by producers and consumers purchased, is the expected demand. The need for soap is a basic human needs in addition to shelter, food, and clothing. Soap is a requirement that health is a necessity of human life. For companies soap, this is an opportunity to attract consumers, producers would have to have other features in addition to product excellence. Marketing is an overall understanding of the sales, trading, distribution. Marketing is one of the activities in the economy and assist in the creation of economic value. While the economic value itself will determine the prices of goods and services for individuals Based on the results of research can be concluded form, with the results of multiple linear regression analysis showed that the beta coefficient for the variable Reference Group (X3) has the largest beta coefficient is equal to 0.442. This indicates that the variable reference group have the greatest influence for making decision in purchasing Nuvo shower soap in District Mlati. In simultaneously External factors consist of variables of Culture (X1), Social Class (X2), Reference Group (X3) and Family (X4) has a significant influence on purchase decisions in the District Mlati Soap NUVO, this can be seen from the results Fcount (31.081 ) larger than Ftable (2.4675). Thus Hypothesis 1 proved. External Factors which partially consists of variables of Culture (X1), Social Class (X2), Reference Group (X3) and Family (X4) has a significant influence on purchase decisions in the District Mlati Soap NUVO, this can be seen from the results of their tcount each variable that is greater than ttable (1.9852). Thus hypothesis 2 proved. Keywords: products, soap, marketing, purchasing.